A novel molecular approach for tracing terrigenous dissolved organic matter into the deep ocean. Issue 5 (14th May 2016) - Medeiros, Patricia M.; Seidel, Michael; Niggemann, Jutta; Spencer, Robert G. M.; Hernes, Peter J.; Yager, Patricia L.; Miller, William L.; Dittmar, Thorsten; Hansell, Dennis A.
Abstract: Marine dissolved organic matter (DOM) contains one of the largest exchangeable organic carbon pools on Earth. Riverine input represents an important source of DOM to the oceans, yet much remains to be learned about the fate of the DOM linking terrestrial to oceanic carbon cycles through rivers at the global scale. Here we use ultrahigh‐resolution mass spectrometry to identify 184 molecular formulae that are indicators of riverine inputs (referred to as t‐Peaks) and to track their distribution in the deep North Atlantic and North Pacific Oceans. The t‐Peaks were found to be enriched in the Amazon River, to be highly correlated with known tracers of terrigenous input, and to be observed in all samples from four different rivers characterized by vastly different landscapes and vegetation coverage spanning equatorial (Amazon and Congo), subtropical (Altamaha), and Arctic (Kolyma) regions. Their distribution reveals that terrigenous organic matter is injected into the deep ocean by the global meridional overturning circulation, indicating that a fraction of the terrigenous DOM introduced by rivers contributes to the DOM pool observed in the deep ocean and to the storage of terrigenous organic carbon. This novel molecular approach can be used to further constrain the transfer of DOM from land to sea, especially considering that Fourier transform ion cyclotron resonance mass spectrometer analysis is becoming increasingly frequent in studies characterizing the molecular composition of DOM in lakes, rivers, and the ocean. Key Points: 184 molecular formulae indicative of riverine inputs (t‐Peaks) have been identified t‐Peaks are correlated with tracers of terrigenous input and observed in multiple rivers worldwide t‐Peaks revealed injection of terrigenous DOM into deep ocean by meridional overturning circulation